Strategi Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Melalui Program Unggulan di SMK Kiyai Mojo Tembelang Jombang - Khoerun Syafi’i; Muhamad Ripin Ikwandi (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2023)
The quality of a school is reflected in its learning programs, which serve as a distinctive brand offered to the community as users of the school’s educational services. This study aims to describe the principal’s strategy for improving the quality of education through the implementation of superior school programs. The research was conducted at Kiyai Mojo Vocational School, Tembelang, Jombang, which applies an excellence-based program focusing on life skills, namely the Sab’ul Matsani Integrated Agriculture Program. This program encompasses farming, gardening, and livestock activities, designed to equip students with practical and entrepreneurial competencies. Using a qualitative research method, data were collected through interviews with the principal and teachers, as well as direct observation and documentation. The collected data were then organized into field notes and interview transcripts, followed by processes of data reduction, presentation, and analysis. The findings reveal that the Sab’ul Matsani Integrated Agriculture Program provides students (santri) with valuable opportunities to design, plan, and implement agricultural processes independently. Participants not only gain theoretical knowledge about agricultural product processing but also understand the growth and development cycles of the materials involved. It is expected that the Sab’ul Matsani program will enhance students’ readiness to face real-world challenges after completing their education in both vocational schools and Islamic boarding schools. Overall, the research concludes that this superior integrated agricultural program has a positive and significant impact on improving the overall quality of education at Kiyai Mojo Vocational School.